Theoretical Aspects of Collective Decision Making - Survey of the Economic Literature; Aspekty teoretyczne kolektywnego podejmowania decyzji - przeglad literatury - Piotr Stanek (Comparative Economic Research. Central and Eastern Europe, 2013)
The article aims at surveying the economic literature related to collective decision making. In order to do so it proposes a coherent framework allowing for a structured analysis of the factors influencing the works of a committee. These factors are divided into external ( shaped outside of the committee e.g. by law) and internal ones (related to the composition of the committee and interactions between its members). The survey of the general economic literature related to collective decision making presented within the proposed framework yields interesting suggestions for further research, including the consequences for the shape of monetary policy committees. – – Artykuł ma na celu dokonanie przegladu literatury ekonomicznej z zakresu kolektywnego podejmowania decyzji. W tym celu zaproponowano ramy pozwalajace na ustrukturyzowana analize czynnikoẃ wpływajacych na prace organu kolektywnego (rady). Dokonano podziału tych czynnikoẃ na zewnetrzne (tzn. kształtowane poza sama rada, np. przez wymogi prawne) oraz wewnetrzne (zwiazane ze składem rady oraz interakcjami miedzy jej członkami). Dokonany w ramach zaproponowanej struktury przeglad literatury ogoĺnoekonomicznej dotyczacej kolektywnego podejmowania decyzji pozwala na zaproponowanie interesujacych kierunkoẃ dalszych badan\', w tym konsekwencji dla kształtu rad polityki pieniezṅej.
Keywords: 330